Reactivation of the Built Environment From Theory to Practice - Fanzini, Daniele; Venturini, Gianpiero (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book deals with urban reactivation, a particular form of regeneration intervention which in addition to the physical-spatial dimension of the places also-and above all-considers the social and relational dynamics that the intervention is able to activate. In this sense, the concept of activation (or reactivation) emphasizes the act of putting something into or back into operation, whether it concerns the material components of a container (a building or a place) or the immaterial components of a content (a need, or a function), starting from the exploitation of opportunities that the architectural project contributes to revealing, developing and accompanying.
Keywords: Buildings-Design and construction; Sociology, Urban; Social service; Regional economics; Spatial economics; Building Construction and Design; Urban Sociology; Social Work; Regional and Spatial Economics